Global, regional, and national burden of liver cancer in adolescents and young adults from 1990 to 2021: an analysis of the global burden of disease study 2021 and forecast to 2040 - Wen, Jingyu; Xia, Mingge; Luo, Han; Zhu, Luwei; Li, Min; Hou, Yifu (Frontiers in Public Health, 2025)
BackgroundThe global burden of liver cancer among adolescents and young adults (AYAs) has often been underestimated, despite significant shifts in its etiology. This study analyzes the disease burden of liver cancer in AYAs from 1990 to 2021 and forecasts trends up to 2040 using data from the Global Burden of Disease Study 2021. Our goal is to provide insights that can inform resource allocation and policy planning.MethodsIncidence, mortality, and disability-adjusted life years (DALYs) data were extracted and estimated annual percentage changes calculated to assess trends. Correlation between age-standardized rates and sociodemographic index (SDI) was analyzed using Spearman correlation, and future trends were predicted using the Bayesian age-period-cohort model.FindingsGlobally, there were 24,348 new liver cancer cases and 19,270 deaths among AYAs in 2021, with decreases in age-standardized rates for incidence, mortality, and DALYs from 1990 to 2021. East Asia bears the highest burden, with males experiencing significantly higher rates than females. The burden increases with age, peaking at 35–39 years. Higher SDI is associated with lower incidence, mortality, and DALYs. While HBV remains the leading cause, NASH is the fastest-growing contributor to liver cancer incidence and mortality. Projections indicate a continued decline in liver cancer burden among AYAs, though female cases are expected to rise.InterpretationDespite a gradual decline in liver cancer burden among AYAs, NASH is emerging as a significant and rising cause of incidence and mortality. Regional and gender disparities persist, highlighting the need for tailored prevention and healthcare strategies to alleviate the liver cancer AYA's burden globally.